The Comparison of Water and Acid Leaching Methods to Reduce Ash and Inorganic Mineral Content in Teak Sawdust Biomass - Saputro, Muhammad Arief; Syamsiro, Mochamad; Megaprastio, Bayu; Ahmad, Noesanto Dewantoro; Herlambang, Bagas (Institut Teknologi Nasional Yogyakarta, 2025)
Biomass is the fourth largest renewable energy source in the world, accounting for approximately 10% of the total global primary energy supply. Every year, a large amount of teak wood sawdust is produced from the manufacturing of furniture, beds, wooden decorations, and various other products. This waste has no economic value and requires considerable storage space, causing problems in handling and disposal. Therefore, utilizing this forestry residue for biofuel production is a sustainable and economically beneficial approach. However, the main challenge in its utilization lies in its high ash and inorganic mineral content, which can reduce energy conversion efficiency and the calorific value of the product. This study aims to compare the effectiveness of washing methods using water and acid solutions in reducing ash content and increasing the calorific value of teak wood sawdust. The research was conducted experimentally in a laboratory, involving several stages: material preparation, washing treatment (water and acid), drying, ash content and calorific value analysis, and result evaluation. The treatments were carried out at mass ratios of 1:25, 1:50, and 1:75, washed for 2 hours using a magnetic stirrer, followed by filtration, rinsing to neutral pH, and drying at 105 °C for 6 hours. The results showed that washing with 1 M HCl consistently produced a greater mass reduction of teak wood sawdust compared to deionized water at all ratios, indicating that the acid method is more effective in reducing the inorganic content of biomass.